Interferential polychromatic filters based on the quasi-periodic one-dimensional generalized multilayer Thue – Morse structures - Bouazzi, Yassine; Kanzari, Mounir (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
In this paper, a new type of optical filter using photonic band gap materials has been proposed. The optical filter was obtained by a combination of periodic H(LH)J and generalized Thue – Morse (GTM) quasi-periodic one-dimensional multilayer. We show that the whole structure H(LH)J[TM]PH(LH)J, where P is the repetition number of the GTM stack, has an interesting application as a polychromatic filter. However, the effect of the repetition number for producing an improved polychromatic filter is presented. So, switches like (on–on–off–off–on–on–…) have been found.
Optica Applicata, Vol. 39, 2009, nr 3, s. 489-498
Keywords: optyka; photonic crystals; periodic; quasi-periodic; Thue – Morse; antitrace map; transmission peak; polychromatic filters